2013
DOI: 10.1002/jpln.201200547
|View full text |Cite
|
Sign up to set email alerts
|

Iron‐reducing bacteria can enhance the activation and turnover of the Fe(III)‐fixed phosphorus for mycorrhizal plants

Abstract: In a greenhouse experiment, Medicago sativa was grown in iron‐rich soil colonized with iron‐reducing bacteria (IRB) and/or Glomus mosseae (GM) under different inorganic phosphorus levels, which was to understand the effects of IRB and GM on the activation and turnover of the Fe(III)‐fixed phosphorus. The results showed that at the both P rates, dual‐inoculation treatment stimulated the hyphal growth and increased the shoot P content. IRB could accelerate mycorrhizal colonization, and showed a positive effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Microorganisms interact in the soil both synergistically and antagonistically to influence the development of colonization and resource competition and acquisition ( Artursson et al, ; Arriagada et al, ; Tanwar et al, ). Previously, we have shown that interactions between IRB and AMF had a positive effect on the infection rate and root colonization of AMF ( Zhang et al., ). It has also shown previously that the contribution of mycorrhizae to plant P uptake may be the greatest under intermediate levels of available P levels, with both low and high levels of P appearing to depress mycorrhizal function ( Chu et al, ).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Microorganisms interact in the soil both synergistically and antagonistically to influence the development of colonization and resource competition and acquisition ( Artursson et al, ; Arriagada et al, ; Tanwar et al, ). Previously, we have shown that interactions between IRB and AMF had a positive effect on the infection rate and root colonization of AMF ( Zhang et al., ). It has also shown previously that the contribution of mycorrhizae to plant P uptake may be the greatest under intermediate levels of available P levels, with both low and high levels of P appearing to depress mycorrhizal function ( Chu et al, ).…”
Section: Discussionmentioning
confidence: 87%
“…Soil microorganisms are the key drivers in soil functional processes ( Cleveland et al., ; Zhang et al, ), such as soil carbon cycling, release and turnover of nutrients, particularly P for subsequent plant capture ( Carney and Matson , ; Van der Heijden et al, ). The releasing of Fe‐P is closely linked to the C‐dependent redox processes of Fe oxide by IRB ( Zhang et al., ). As a biogeochemical redox agent, IRB can increase the mineralization of soil organic matter and enhance the nutrient availability, especially P from Fe‐P in subtropical soils ( Chacón et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations